Fecal Microbiota Transplantation for the Treatment of Inflammatory Bowel Disease: An Update - Tan, Pufang; Li, Xiaogang; Shen, Jun; Feng, Qi (Frontiers in Pharmacology, 2020)
Fecal microbiota transplantation (FMT) has successfully been applied for the treatment of recurrent Clostridioides difficile infection (CDI), which has led to studies on its application to other gastrointestinal diseases and extraintestinal diseases associated with gut microbiota dysbiosis. Recently, the results of FMT for patients with inflammatory bowel disease (IBD) have been encouraging. However, studies have not fully clarified the clinical application of this emerging therapy. Here, we aimed to review the current knowledge in this fast-growing field and characterize the techniques, mechanisms, efficacy, and safety of FMT for the treatment of IBD patients.